1998
DOI: 10.1175/1520-0477(1998)079<0221:ivoapi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variations of Annual Precipitation in the Central United States

Abstract: Century-long annual precipitation time series at 168 stations in the central United States are analyzed with special attention given to interdecadal variations. The results show statistically significant precipitation variations of interdecadal timescales in the region. In particular, one variation has a quasi 20-yr period, and another one possesses a quasi 12-yr period. The negative phases of the 20-yr variation match with the major drought periods in the region's history, that is, the 1910s, 1930s, 1950s, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…Hu et al (1998) connect the interdecadal variation in annual precipitation of the central United States to the North Atlantic and Higgins et al (2000) find Arctic oscillation-related contributions to the seasonal predictability of summer precipitation to be significant in the upper Midwest. Most recently, Ruiz-Barradas and Nigam (2005) and Weaver and Nigam (2008) find strong correlations between the activity of the GPLLJ, central US precipitation, and the NAO index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al (1998) connect the interdecadal variation in annual precipitation of the central United States to the North Atlantic and Higgins et al (2000) find Arctic oscillation-related contributions to the seasonal predictability of summer precipitation to be significant in the upper Midwest. Most recently, Ruiz-Barradas and Nigam (2005) and Weaver and Nigam (2008) find strong correlations between the activity of the GPLLJ, central US precipitation, and the NAO index.…”
Section: Discussionmentioning
confidence: 99%
“…The authors find negative phases of the NAO to coincide with stronger than expected influx of Gulf air into the US interior and unseasonably high (low) precipitation in the Midwest (southeast), summer conditions that were observed during both the 1993 and 2008 events. Hu et al (1998) and Ruiz-Barradas and Nigam (2005) argue that the GPLLJ strength and activity are related to the southerly branch of the Bermuda High centred over the North Atlantic known to be impacted by the state of the NAO. The storms that are generated from the interaction between this GPLLJ and the mid-latitudinal westerly jet significantly influence the precipitation development in the Central Plains region, as observed during the sustained phases of both the 1993 and 2008 floods.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the trend analysis is based on the Hu et al (1998) method. The 11 year running mean is a filtering method.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of the trend is based on the M-K rank statistical test and fitting method of Hu et al (1998). M-K rank statistics, which make no assumption about the probability distribution of the original data, are tested for significance using a standard normal distribution.…”
Section: Trend Analysismentioning
confidence: 99%
“…Conversely, the 1990s were some of the wetter years on record for the Missouri River Basin. Hu et al (1998) reported that the amount of annual precipitation generally declined from the 1880s through the mid 1960s and then began an upward trend in the lower Missouri River basin states of Nebraska, Kansas, and Missouri (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%